ENT 600: Smart window / Anis Amirah Jamal, Noor Aida Yeop Sulaiman and Sharifah Naziyah Syed Putra - Jamal, Anis Amirah; Yeop Sulaiman, Noor Aida; Syed Putra, Sharifah Naziyah (2018)
The team are going to produce an innovative product called "Smart Window". Smart window can contribute to fulfil the requirement of public needs. Smart window can help the community and at the same can improve the mall services. From the prediction, the "Smart Window" are going to be provided in every shopping mall area especially supermarket.